Valgo dinâmico do joelho durante step down lateral e corrida em mulheres corredoras com dor patelofemoral e assintomáticas - Vasconcelos, Diego Protasio de (2022)
INTRODUCTION: Frontal plane knee kinematics alterations, as dynamic knee valgus (DKV), have been associated with patellofemoral pain (PFP) in female runners. DKV is usually quantified by the frontal plane knee projection angle (FPPA) through two-dimensional (2D) video analysis during squat tests. But, it’s still unclear whether these tests actually reflects knee kinematics during running. OBJECTIVES: The aims of this cross-sectional study were to compare and to correlate the DKV, measured by the FPPA, during lateral step down (LSD) squat test and running in asymptomatic and PFP female runners. METHODOLOGY: A 2D video analysis to determine FPPA was conducted in 21 asymptomatic female runners and 17 PFP female runners during LSD and running. Pearson’s correlation test, independent t-tests and a factorial ANOVA with Bonferroni post hoc correction were used for statistical analysis. RESULTS: The FPPA recorded during LSD was significantly higher than during running in asymptomatic (16.32° ± 5.38 vs 4.02° ± 3.26, p < 0.01) and PFP female runners (17.54° ± 7.25 vs 4.64° ± 3.62, p < 0.01). No significant differences were found in FPPA values between asymptomatic and PFP runners during LSD (16.32° ± 5.38 vs 17.54° ± 7.25, p = 0.55) and running (4.02° ± 3.26 vs 4.64° ± 3.62, p = 0.58). In both groups, Pearson's correlation test showed only a small (r < 0.3) and non-significant (p > 0.05) correlation of the FPPA between LSD and running. CONCLUSION: According to our results, DKV was not similar during LSD and running, and there was no significant correlation in FPPA values between the LSD test and running in both groups. Therefore, the LSD test should be used with caution in clinical practice to evaluate DKV in female runners with and without PFP.